2021
DOI: 10.2147/dddt.s292243
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum ZS62 Alleviates Alcohol-Induced Gastric Injury in Mice via an Anti-Oxidative Mechanism

Abstract: Aim Gastric mucosal injury is a typical characteristic of gastric diseases. The prevalence of gastric mucosal injury caused by alcohol has been on the rise, which has been considered a serious problem. The purpose of this study is to explore the protective effect on gastric injury of Lactobacillus plantarum ZS62 (LP-ZS62) isolated from naturally fermented yak yoghurt. Methods We established a gastric injury model through alcohol and evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
1
10
2
Order By: Relevance
“…The increased SOD-1 expression that we observed led us to study whether supplementation with Prodefen ® could increase in the Nrf2-antioxidant enzyme pathway. First, we observed that the expression of Nrf2 was similar in both experimental groups, contrasting with previous reports [64,91,92], while we found a greater phosphorylation of this transcription factor in arteries from SHR-SYNB animals. The different experimental models (heart, gastric mucosa, or cell cultures) or supplementation (probiotics and prebiotics) used could explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…The increased SOD-1 expression that we observed led us to study whether supplementation with Prodefen ® could increase in the Nrf2-antioxidant enzyme pathway. First, we observed that the expression of Nrf2 was similar in both experimental groups, contrasting with previous reports [64,91,92], while we found a greater phosphorylation of this transcription factor in arteries from SHR-SYNB animals. The different experimental models (heart, gastric mucosa, or cell cultures) or supplementation (probiotics and prebiotics) used could explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with prior findings, the administration of ethanol in rats resulted in a considerable elevation in gastric issue’s MDA levels [ 26 , 27 ]. High ethanol intake produces substantial ROS, which react with membrane lipids to produce lipid peroxides [ 28 ]. Several investigations have indicated that antioxidant substances that scavenge free radicals prevent ethanol-induced stomach ulcers [ 26 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Lactobacillus plantarum KSFY06 downregulated the Keap1 expression and upregulated the Nrf2 mRNA expression in D-galactose-induced mice ( Li et al., 2021 ). Lactobacillus plantarum DP189 could upregulate the Nrf2 level and the mRNA level of antioxidant enzymes ( Wu et al., 2021 ), which further improved the neurodegeneration in PD ( Wang et al., 2022 ). Our results suggested that PP could regulate the Nrf2 pathway in exerting an antioxidant role in PD.…”
Section: Discussionmentioning
confidence: 99%